2014
DOI: 10.1080/08997659.2014.893460
|View full text |Cite
|
Sign up to set email alerts
|

Association of Mitochondrial Dysfunction with Oxidative Stress and Immune Suppression in Blunt Snout Bream Megalobrama amblycephala Fed a High‐Fat Diet

Abstract: High-fat diets may have favorable effects on growth, partly based on protein sparing, but high-fat diets often lead to fatty liver (excessive fat deposition in the liver), which may be deleterious to fish growth and health. The goal of this study was therefore to investigate possible adverse effects and how they develop. Juvenile Blunt Snout Bream Megalobrama amblycephala (initial weight ± SE = 17.70 ± 0.10 g) were fed two diets (5% fat [control] or 15% fat). After 8 weeks, fish that were fed the 15% fat diet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 60 publications
7
31
0
Order By: Relevance
“…This indicated that a long‐term intake of high‐fat diets could enhance lipogenesis but inhibit lipolysis. Those results were in accordance with previous studies on this species (Lu, Xu, Liu, et al, ; Lu, Xu, Wang, et al, ; Xu et al, ). This result may be explained by two assumptions: (a) SREBP1, a key transcriptional factor involved in lipogenesis (Spiegelman & Flier, ), mediated TG synthesis by the regulation of genes involved in lipogenesis and lipid storage, mainly in the liver (Horton, Goldstein, & Brown, ), such as ACCα which is closely involved in FA biosynthesis (Castro et al, ).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…This indicated that a long‐term intake of high‐fat diets could enhance lipogenesis but inhibit lipolysis. Those results were in accordance with previous studies on this species (Lu, Xu, Liu, et al, ; Lu, Xu, Wang, et al, ; Xu et al, ). This result may be explained by two assumptions: (a) SREBP1, a key transcriptional factor involved in lipogenesis (Spiegelman & Flier, ), mediated TG synthesis by the regulation of genes involved in lipogenesis and lipid storage, mainly in the liver (Horton, Goldstein, & Brown, ), such as ACCα which is closely involved in FA biosynthesis (Castro et al, ).…”
Section: Discussionsupporting
confidence: 94%
“…In addition, an increase in cytochrome c in the cytosol of fish from the high‐fat diet group was indicative of cytochrome c release from the mitochondria, indicating a change in the permeability of the mitochondrial membrane. Those data were in accordance with previous studies on this species (Lu, Xu, Liu, et al, ). However, simvastatin supplementation reduced cytochrome c content in the cytoplasm of blunt snout bream fed high‐fat diet.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In the recent years, there has been a tendency of utilizing lipid‐rich diets in intensive aquaculture, because higher growth rates can be achieved by increasing dietary lipids above their minimum levels, probably as a result of protein sparing and improved feeding efficiency (Boujard et al, ; Lu et al, ). However, there will also be an upper limit that, if exceeded, will result in unwanted deposition of lipids in the tissues due to an imbalance of nutrient and energy supplies, and may negatively affect survival, growth, disease resistance, stress response and lipid metabolism (Chen et al, ; Company, Calduch‐Giner, Kaushik, & Perez‐Sanchez, ; Gaylord & Gatlin, ; Li et al, ; Lu et al, ; Regost et al, ; Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, liver lipid of bullfrog fed the CHO/L 1.82 and 1.20 diets were significantly higher than that of other groups. It is reported that dietary lipid toward an upper limit often leads unwanted deposition in the liver referred as fatty liver, inducing anomalies of metabolism and physical properties (Rueda‐Jasso, Conceição, Dias, Coen, Gomes, Rees, Soares, Dinis & Sorgeloos ; Lu, Xu, Li, Li, Huang & Liu ; Lu, Xu, Liu, Wang, Zhang & Li ).…”
Section: Discussionmentioning
confidence: 99%